A gradient relationship between low birth weight and IQ: A meta-analysis. Issue 1 (December 2017) - Gu, Huaiting; Wang, Lixia; Liu, Lingfei; Luo, Xiu; Wang, Jia; Hou, Fang; Nkomola, Pauline; Li, Jing; Liu, Genyi; Meng, Heng; Zhang, Jiajia; Song, Ranran
Abstract Multiple studies have reported that individuals with low birth weights (LBW, <2500 g) have a lower intelligence quotient (IQ) than those with normal birth weights (NBW, ≥2500 g). Based on 57 eligible individual studies including 12, 137 participants, we performed a meta-analysis to estimate the association between low birth weight and individuals' IQ scores (IQs). The pooled weight mean difference (WMD) in IQs between NBW and LBW individuals was 10 (95% CI 9.26–11.68). The WMD was stable regardless of age. No publication bias was detected. The mean IQs of the extremely low birth weight (ELBW, <1000 g), very low birth weight (VLBW, 1000–1499 g), moderately low birth weight (MLBW, 1500–2499 g) and NBW individuals were 91, 94, 99 and 104, respectively. Additionally, the WMD in IQs with NBW were 14, 10 and 7 for ELBW, VLBW, and MLBW individuals, respectively. Two studies permitted estimates of the influence of social determinants of health to the discrepancy in IQs, which was 13%. Since IQ is inherited and influenced by environmental factors, parental IQs and other factors contribute to residual confounding of the results. As the conclusion was based on population studies, it may not be applicable to a single individual.